Model Integrasi Sistem Manajemen Radiologi Digital untuk Peningkatan Efisiensi dan Akurasi Pelayanan Diagnostik - Bisra, Marido; Tonis, Marian; Handoko, Bobi (Journal of Hospital Administration and Management (JHAM), 2025)
The increasing complexity of diagnostic imaging services raises critical questions regarding how digital integration can improve the efficiency and accuracy of radiology management systems. Although digital technologies such as Radiology Information System and Picture Archiving and Communication System have been widely implemented, many healthcare institutions still experience fragmented workflows, reporting delays, and administrative errors. This study aimed to develop an integrated digital radiology management system model to optimize diagnostic service workflows. The research employed a system modeling and evaluation approach involving patient registration, image acquisition, reporting, and diagnostic information distribution processes. The results demonstrated that the implementation of the proposed integration model reduced patient registration time from 12 minutes to 5 minutes (58.3%), shortened image acquisition and transfer time from 18 minutes to 9 minutes (50.0%), and decreased report turnaround time from 45 minutes to 22 minutes (51.1%). Administrative error rates declined from 8.2% to 2.1%, while diagnostic report distribution accuracy increased from 89.4% to 98.7%. These findings indicate that digital system integration significantly enhances operational efficiency and diagnostic accuracy through structured data management and real-time information accessibility. This study concludes that the integration of digital radiology management systems represents a strategic solution for improving effective, accurate, and patient-centered diagnostic healthcare services